Peningkatan Kompetensi Profesional MGMP Kimia Kabupaten Pasaman Sebagai Pembina Siswa Menghadapi Olimpiade Sains Nasional (OSN) - Edi Nasra; Fajriah Azra; Zonalia Fitriza; Riga Riga; M. Iqbal S.G; Tessa Faradilla; Ahmad Raisan R.P (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPROVİNG THE PROFESSİONAL COMPETENCE OF MGMP CHEMİSTRY İN PASAMAN REGENCY AS STUDENT COACHES FACİNG THE NATİONAL SCİENCE OLYMPİAD (OSN). Teacher training for National Science Olympiad (OSN) coaches is carried out as an effort to improve the professional competence of the Pasaman Regency Chemistry MGMP to prepare students to take part in competitions at the district and provincial levels. The ability of teachers prior to participating in the training was identified using pre-tests originating from OSN questions for the last five years. The training was carried out through analysis of OSN-K (City/District Level) and OSN-P (Provincial Level) questions for the last 5 years in 5 groups, and each group made written discussions which were compiled into modules that could be used by the trainees to prepare students in their respective schools. After that, discussions on HOTS questions in the fields of Inorganic Chemistry, Organic Chemistry, Physical Chemistry, Analytical Chemistry and Biochemistry were given by the resource persons. At the end of the activity, a final test is given to see the effectiveness of the training. The results of the pre-test and post-test showed an increase in participants' understanding of 23.51. In addition, the response to the activity evaluation questionnaire obtained an average questionnaire of 3.47 (scale 4), which means that the training is in the good category.